Efeitos da flutamida na morfologia dos órgãos reprodutivos e fígado de Rhinella schneideri (Anura: Bufonidae) - Gregorio, Lara Salgueiro de [UNESP] (2015)
The anurans are in population decline worldwide, and water pollution is one of the factor influencing this process. The Flutamide is an antiandrogen medicine used against prostate cancer, and also is a contaminant. This compound can act as an endocrine disrupter that can affect mainly the reproduction. In Bufonidae family occurs a peculiar organ named Bidder's organ, considered a rudimentary ovary. The liver is the main organ with detoxification functions and is directly related to substances metabolism. Thus, our aim was to evaluate the effect of Flutamide on morphology of the reproductive organs and liver of males Rhinella schneideri, and on the serum levels of steroid hormones. We used 18 males of the specie, organized in 3 groups. The treatment groups received, for 7 days, daily doses of 1 or 5 mg/kg of Flutamide diluted in mineral oil, while the control group received only the mineral oil. After the experiments, the animals were euthanized, the blood was collected and testis, Bidder's organs and liver were removed and proceed to histological routine according to the analysis employed for each one. For testis we evaluated the area of the germ cells and seminiferous locule. For Bidder's organ we quantified the the germ cells and the pigmented area of lipofuscin. In the liver we measured the pigmented areas of melanin, lipofuscin and hemosiderin. Serum testosterone and estradiol were identified by ELISA. In testis there was an increase in spermatogonia and reduction of bundle and lumen sperm in both treatments. Also occurred an increase in secondary spermatids in lower dosage and in primary spermatocytes in higher dosage. The locular area varied only at the low dose. In Bidder's organ there was a decrease in degeneration and atresia oocytes and an increase in final diplotene oocytes in both concentrations of Flutamide, as well as a reduction in lipofuscin pigmented area. In the liver the 3 ...